2021
DOI: 10.3389/fnbot.2021.651432
|View full text |Cite
|
Sign up to set email alerts
|

Generative Models for Active Vision

Abstract: The active visual system comprises the visual cortices, cerebral attention networks, and oculomotor system. While fascinating in its own right, it is also an important model for sensorimotor networks in general. A prominent approach to studying this system is active inference—which assumes the brain makes use of an internal (generative) model to predict proprioceptive and visual input. This approach treats action as ensuring sensations conform to predictions (i.e., by moving the eyes) and posits that visual pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
51
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(54 citation statements)
references
References 165 publications
3
51
0
Order By: Relevance
“…Moreover, in a discrete state space setting, it is often tractable to explicitly evaluate the integral over time and compute the optimal plan posterior since agents in discrete states typically exist in small enough environments such that all policies can be explicitly enumerated and evaluated [71]. Discrete state space active inference has been widely applied in computational neuroscience to simulate choice behaviour, e.g., saccades [76] and exploratory behaviour [68].…”
Section: A Discrete-state-spacementioning
confidence: 99%
“…Moreover, in a discrete state space setting, it is often tractable to explicitly evaluate the integral over time and compute the optimal plan posterior since agents in discrete states typically exist in small enough environments such that all policies can be explicitly enumerated and evaluated [71]. Discrete state space active inference has been widely applied in computational neuroscience to simulate choice behaviour, e.g., saccades [76] and exploratory behaviour [68].…”
Section: A Discrete-state-spacementioning
confidence: 99%
“…Active inference extends predictive coding models of perception to the use of action to minimize future prediction errors (Friston, 2005;Parr & Friston, 2018. In addition to revising their generative model, a Bayesian agent can minimize prediction errors through movements (e.g., see the use of vision to minimize surprisal; Parr et al, 2021) or can actively change the world into the predicted state (Adams et al, 2013;Sarpeshkar et al, 2017). Harris et al (2021) have recently suggested that active inference can enhance our understanding of skilled anticipation by providing a principled account of how actions are used to optimize predictions, as well as accounting for decision making via Bayesian inference.…”
Section: Illustration Of Bayesian Probabilistic Integrationmentioning
confidence: 99%
“…An additional benefit of Bayesian brain and active inference frameworks is that they are rooted in computational models of perceptual processes (Adams et al, 2015;Parr et al, 2021;Smith et al, 2020). These models formalise active inference, and the process of Bayesian belief updating, making mechanistic explanations potentially clear and testable.…”
Section: Illustration Of Bayesian Probabilistic Integrationmentioning
confidence: 99%
See 1 more Smart Citation
“…the variational free energy [5]. In [18], Parr et al propose a model for (human) vision, which considers a scene as a factorization of separate (parts of) objects, encoding their identity, scale and pose. This is in line with the so called two stream hypothesis, which states that visual information is processed by a dorsal ("where") stream on the one hand, representing where an object is in the space, and a ventral ("what") stream on the other hand, representing object identity [4].…”
Section: Introductionmentioning
confidence: 99%